Logics of spatial location of the banking sector and spatial practices of users in Campos dos Goytacazes-RJ - Santos, Samuel Henderson de Faria (2023)
In the midst of changes in economic, social and technical organization since the late twentieth century, companies sought to articulate differently, acting in a decentralized way, but connected through networks. With the banking sector was no different, branches and headquarters change both in terms of forms and spatiality at multiple scales. The advances in the technical structure that allow banks to deconcentrate and spread throughout the territory are concomitant to the main changes in capitalism, which, through the advances of networks, increases their reach and circulation. This work aims to understand the location logics of large banks and their implications on the spatial practices of users of banking services in the city of Campos dos Goytacazes/ RJ between the mid-2000s and 2020. Our main results show a national trend of decreasing branches, something that is also reflected in Campos dos Goytacazes, where branches are located in the most profitable centralities for banks, especially because they are close to the center and the circulation axes.